1966
DOI: 10.1172/jci105384
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of clotting factors by the isolated perfused rat liver.

Abstract: The liver has been proposed as a site of synthesis of blood-clotting factors, in part because of the demonstrated dominant role of the liver in synthesis of all plasma protein fractions except the y-globulins (1, 2). In addition, observations after hepatectomy (3, 4) and hepatic injury (5, 6) and in hepatic disease (7,8) have provided a body of evidence consistent with hepatic synthesis of fibrinogen, prothrombin, and Factors V, VII, IX, and X. This evidence, however, has not been considered definitive, mainly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

1970
1970
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(29 citation statements)
references
References 26 publications
1
28
0
Order By: Relevance
“…Although it appeared that procoagulant activity persisted longer than tissue factor activity, the procoagulant activity was completely inhibited by incubation with the antibody to tissue factor. In all experiments where tissue factor was generated by the lymphocytes, the material was completely inhibited by the rabbit antihuman tissue factor antibody (Table II) (47,48), the site of production of factor VIII is unknown. Perfusion studies of livers and spleens (23)(24)(25) have revealed variable amounts of factor VIII activity in the perfusates.…”
Section: Methodsmentioning
confidence: 99%
“…Although it appeared that procoagulant activity persisted longer than tissue factor activity, the procoagulant activity was completely inhibited by incubation with the antibody to tissue factor. In all experiments where tissue factor was generated by the lymphocytes, the material was completely inhibited by the rabbit antihuman tissue factor antibody (Table II) (47,48), the site of production of factor VIII is unknown. Perfusion studies of livers and spleens (23)(24)(25) have revealed variable amounts of factor VIII activity in the perfusates.…”
Section: Methodsmentioning
confidence: 99%
“…Table 2, the administration of cycloheximide again prevented the incorporation of amino acids into the prothrombin produced after the administration of the antibiotic. There was a substantial incorporation of ['Hiaminoacids before cycloheximide and vitamin K treatment, and an insignificant (5,13,25,26). It is significant that the rapid initial burst of prothrombin seen in deficient animals after vitamin K administration (3,6,12) is not seen in the liver-perfusion studies, and that cycloheximide does block prothrombin production in vitamin K-deficient rats during the second hour after vitamin administration (12).…”
Section: Amino-acid Incorporation Into Prothrombinmentioning
confidence: 98%
“…Generation of factor V by the isolated liver also has been reported [2,6,9], but peak activities often were followed by disappearance of the coagu lant activity. Because, unlike human factor V, rat factor V is stable, its purported degradation during perfusion is curious.…”
Section: Introductionmentioning
confidence: 58%
“…The isolated rat liver generates the well-established vitamin K.-dependent factors: prothrombin and factors VII, IX, and X [3,5,6]. Other techniques, such as rat liver slices and liver homogenates, are confirmatory.…”
Section: Introductionmentioning
confidence: 99%